Pengaruh Media Sosial dan Persepsi Risiko terhadap Kepercayaan Konsumen pada Produk Kosmetik - Noviana Febriani; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the effect of social media and perceived risk on consumer trust in cosmetic products. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to respondents, namely Management students of the 2022 cohort at Universitas Muhammadiyah Bandung, selected using purposive sampling. Data analysis was conducted using multiple linear regression, along with classical assumption tests, t-test, and coefficient of determination (R²). The results indicate that social media has a positive and significant effect on consumer trust, whereas perceived risk has a negative and significant effect on consumer trust. Simultaneously, social media and perceived risk significantly influence consumer trust. This research is expected to contribute theoretically to the development of consumer trust studies and practically to cosmetic industry practitioners in designing effective social media marketing strategies while managing perceived risks.